Uma visão sobre as “Diretas Já” através do jornal A Tribuna (1983-1984) - Gauer, Ricardo Felipe (2024)
The analysis of speeches published in the press is essential to understand not only historical events, but also the representations and interpretations that were constructed in certain contexts. In this sense, this research aims to central objective to analyze the speeches published in the newspaper A Tribuna about the movement of Diretas Já, which marked the Brazilian political period, specifically in the months of November from 1983 to April of the following year. Based on this theme, we propose to answer the following question: How did the newspaper A Tribuna approach the Diretas Já movement (1983-1984) in his speeches and what was his position and influence in this political context specific? Thus, assuming that newspapers are not merely storytellers, but builders of meanings and interpretations, it is believed that speeches reported by the newspaper A Tribuna during the Diretas Já period, reflect no only the textual content related to facts that occurred, but also to visions and political and ideological positions of that time. As a basis for carrying out this research, primary sources will be used such as editions of the newspaper A Tribuna, documents historical references to the Diretas Já movement, and secondary sources that address the Brazilian political history from a perspective of the 1980s and the press' dealings with History. The methodology used will be Discourse Analysis, to search for the different speeches that the newspaper A Tribuna issued about Diretas Já.